Fenway Park fire, 1934 - Boston Globe (Tufts Archival Research Center, 2005)
Street-level view of fire that destroyed much of Fenway Park. Smoke is billowing from the building, fire engines are on the street outside the building. Several fire hoses are spraying water on the buildings in the area. Firemen are seen in the area as well as onlookers. 10 1/8 x 13 3/8 Photographs